Employer demand intelligence - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
It is very important to have a clear picture of the job market at any time—not only for governments for timely decision making but also for scenarios like individuals doing career planning. Furthermore, due to the volatile and dynamic nature of the job market it is essential that the information about employer demand is up-to-date. This information can be collected from job advertisements and published on the web. However, the job advertisements usually contain unstructured information in textual form, with frequent usage of specific jargon related to the nature and field of the advertised vacancy.